SKALA PRIORITAS USULAN PENANGANAN JALAN DALAM UPAYA STRATEGI PENINGKATAN KEMANTAPAN JALAN - Risnandar, Risnandar Nurdianto; Budiman, Dedi (JITSi : Jurnal Ilmiah Teknik Sipil, 2023)
Abstract - The stability of roads is one of the important indicators in supporting connectivity and smooth transportation, which directly impacts the economy and the welfare of the community. Therefore, an appropriate road management strategy is needed to enhance road stability in order to support the acceleration of economic growth and equitable development in Tasikmalaya Regency. The aim of this research is to establish a priority scale for road handling proposals based on resource and budget constraints. The method used involves criterion-based analysis such as road criteria that support access to basic service facilities, economic centers in the form of agricultural and fisheries production centers, trade and tourism industries, smooth road programs, transportation infrastructure node facilities, connectivity in provincial border areas, as well as supporting programs outlined in presidential regulations. By using the Analytic Hierarchy Process (AHP) method, the proposed road handling is ranked based on its weight level. Data was collected through interviews and questionnaires with policymakers/stakeholders. From the data analysis, the results of the criteria weights are as follows: the criterion supporting access to basic service facilities (0.37), the criterion supporting access to economic centers in the form of agricultural and fishery production centers, industry, trade, and tourism (0.24), the criterion supporting the smooth road program (0.08), the criterion supporting access to transportation infrastructure hubs (0.16), the criterion supporting connectivity in provincial border areas (0.09), and the criterion supporting programs in presidential regulations. (0,07). The order of road segments based on priority for handling proposals is Papayan - Cikalong, Warungpeuteuy - Taraju, Sindangreret - Cidadap, Pasirgintung - Lengkongbarang, Cirendeu - Cihanura, Taraju - Bojonggambir, and Warunglegok - Cikeusal.  Keywords: Steady Road, AHP, Treatment Priority Scale Abstrak – Kemantapan jalan merupakan salah satu indikator penting dalam mendukung konektivitas dan kelancaran transportasi, yang berdampak langsung pada perekonomian serta kesejahteraan masyarakat. Oleh karena itu, diperlukan strategi penanganan jalan yang tepat untuk meningkatkan kemantapan jalan guna mendukung akselerasi pertumbuhan ekonomi dan pemerataan pembangunan di Kabupaten Tasikmalaya. Tujuan dari penelitian ini adalah untuk menyusun skala prioritas usulan penanganan jalan yang berbasis pada keterbatasan sumber daya dan anggaran. Metode yang digunakan melibatkan analisis berbasis kriteria seperti kriteria jalan yang mendukung askses fasilitas pelayanan dasar, pusat perekonomian berupa sentra produksi pertanian dan perikanan, perindustrian perdagangan dan pariwisata, program jalan mulus, fasilitas simpul infrastruktur transportasi, konektivitas di kawasan perbatasan provinsi serta mendukung program yang ada dalam peraturan presiden. Dengan menggunakan metode Analytic Hierarchy Process (AHP) usulan penanganan jalan diurutkan berdasarkan tingkat bobotnya. Data dikumpulkan dengan wawancara dan kuisioner dengan pemangku kebijakan/Stakeholder. Dari analisis data, diperoleh hasil bobot kriteria yaitu kriteria mendukung akses fasilitas pelayanan dasar (0,37), kriteria mendukung akses pusat perekonomian berupa sentra produksi pertanian dan perikanan, perindustrian perdagangan dan pariwisata (0,24), kriteria mendukung program jalan mulus (0,08), kriteria mendukung akses fasilitas simpul infrastruktur transportasi (0,16), kriteria mendukung konektivitas di kawasan perbatasan provinsi (0,09), kriteria mendukung program dalam peraturan presiden (0,07). Urutan Ruas Jalan skala prioritas usulan penanganan jalan adalah Papayan - Cikalong, Warungpeuteuy - Taraju, Sindangreret - Cidadap, Pasirgintung - Lengkongbarang, Cirendeu - Cihanura, Taraju - Bojonggambir dan Warunglegok - Cikeusal.   Kata kunci: Kemantapan Jalan, AHP, Skala Prioritas Penanganan.